Regarding adding drawings of elevator switch box and wiring tube of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding adding drawings of elevator switch box and wiring tube of BRAC University new campus project.